Influence of cigarette smoking and inflammatory gene polymorphisms on glycated hemoglobin in the Japanese general population - Nishida, Yuichiro (Prev Med Rep, 2016)
OBJECTIVE: Inflammation is closely involved in the development of type 2 diabetes, and cigarette smoking acts as potent inducer of inflammation. We therefore investigated interactions between inflammation-related gene polymorphisms and cigarette smoking on glycated hemoglobin (HbA(1c)) in the Japanese general population. METHOD: We conducted a cross-sectional study using data collected from 2619 Japanese (1274 males and 1345 females) 40–69 years of age who participated in baseline survey of the Japan Multi-Institutional Collaborative Cohort (J-MICC) Study (2005–2008). Eight polymorphisms in seven genes (interleukin [IL]-1β, IL-2, IL-4, IL-8, IL-10, IL-13 and tumor necrosis factor-α) were determined using the Invader assay. The interactions of smoking and gene polymorphisms on HbA(1c) levels were analyzed using multiple linear and logistic regression models and analysis of covariance with adjustment for potential confounders. RESULTS: Among the eight polymorphisms, only one significant interaction was detected for IL-1β T-31C (P < 0.0001). Among the subjects carrying TT genotype, current heavy smokers (≥ 20 cigarettes/day) had higher HbA(1c) (5.83 [95% confidence interval 5.67–5.99] %) versus all other smoking status groups (never 5.49 [5.41–5.56] %, former 5.54 [5.43–5.65] %, current moderate [< 20 cigarettes/day] 5.50 [5.30–5.69] %), whereas such differences were not observed in the subjects with C allele. The logistic regression analyses regarding high-normal HbA(1c) levels showed a similar pattern of results. CONCLUSION: Smoking status did not interact with any other inflammation-related polymorphisms except for IL-1β T-31C. Heavy smokers harboring the TT genotype of IL-1β T-31C polymorphism show a greater adverse effect of smoking on HbA(1c) levels among Japanese middle-aged subjects.